Evaluation of caesarean rates according to Robson classification using a newly developed smart phone application in a tertiary center in Sri Lanka: a comparative study - Chandana Jayasundara; Indunil Piyadigama; Asanka Jayawardane; Ananda Perera (BMC Pregnancy and Childbirth)
Abstract Objective Caesarean section (CS) rates in Sri Lanka have escalated significantly, with projections indicating that over half of all births may involve CS by 2025. To address this rise and mitigate maternal morbidity, it is essential that CS procedures are medically justified. This study evaluates RobsApp®, a novel smartphone application designed to collect high-quality prospective data on CS rates based on the Robson classification. Methods The study utilized RobsApp® for data collection in the Professorial Unit of De Soysa Hospital for Women (DSHW), Sri Lanka. Data were collected prospectively from 1,712 deliveries between April and October 2019. The analysis focused on CS rates across different Robson categories and the quality of the collected data, comparing them with previous data obtained using traditional methods. Results The overall CS rate was 33.0%, with Robson category 5a accounting for most cases. Emergency CS constituted 49.6% of all procedures, with cardiotocograph (CTG) abnormalities being the leading indication. The quality of the data collected through RobsApp® met the standards recommended by the Robson guidance, as evidenced by the study's ability to accurately categorize deliveries and assess CS rates. Conclusions RobsApp® has proven to be an effective tool for prospective data collection, aligning well with Robson guidelines and facilitating high-quality data gathering. The study reveals a rising trend in CS rates at DSHW, particularly for reasons beyond previous CS. The inclusion of demographic data and birth weight analysis in future studies will enhance comparisons and insights into reducing CS rates. Ethics Ethical approval was obtained from the Ethical Review Committee, Faculty of Medicine, University of Colombo (Ref – EC-19–024) which waived the need for individual consent. Study adhered to the Helsinki Declaration.